Caribou Hunters in the Western Arctic : Zooarchaeology of the Rita-Claire and Bison Skull Sites - Morrison, David A. (Book collections on Project MUSE., 1997)
"The Rita-Claire and Bison Skull sites offer glimpses into a poorly known aspect of Inuvialuit life, namely, the autumn trek away from the coast to procure caribou meat, hides, and other materials. Through a detailed study of the caribou bones found at these sites, we are offered a better understanding not only of Inuvialuit life but also of the strengths and weaknesses of current methods of zooarchaeological analysis. The study explores many aspects of site formation processes, factors that condition the composition of bone assemblages, methods for inferring the age and sex of caribou skeletons, and the implications of these findings for understanding Inuvialuit history. Many of these topics are relevant to all studies of large animal bone assemblages"--Jacket.